Fabrication of a polyvinylidene fluoride tree-like nanofiber web for ultra high performance air filtration. Issue 94 (23rd September 2016) - Li, Zongjie; Kang, Weimin; Zhao, Huihui; Hu, Min; Ju, Jingge; Deng, Nanping; Cheng, Bowen
Abstract : A novel polyvinylidene fluoride tree-like nanofiber web for high performance air filtration was successfully fabricated via one-step electrospinning. Abstract : A novel polyvinylidene fluoride (PVDF) tree-like nanofiber web was successfully fabricated via one-step electrospinning. The effect of the tree-like structure on the pore size distribution and specific surface area were measured, and the filtration properties of the tree-like nanofiber webs with different basis weights were investigated. The results showed that the tree-like structure significantly decreased the pore size and narrowed the range of pore size distribution, and dramatically enhanced the specific surface area. In comparison with common PVDF nanofiber webs, the tree-like nanofiber webs exhibited excellent filtration performance. The filtration efficiency of the tree-like nanofiber webs with the basis weight of 1 g m −2 to 0.26 μm NaCl particles was 99.999% and the pressure drop was only 124.2 Pa which was comparable to ultra low penetration air filters (ULPA). The tree-like nanofiber webs will be widely used in the field of high efficiency and precision filter materials and medical protective materials.